Three Dimensions of Social Media Messaging Success by Environmental NGOs. Issue 3 (3rd April 2019) - Comfort, Suzannah Evans; Hester, Joe Bob
ABSTRACT: Studies show that NGOs persist in using social media to impart unidirectional messages rather than taking advantage of the participatory nature of networked media. Fear of a loss of message control may be at the heart of NGOs' desire to keep social media messages on track. The current study examines the success of an environmental NGO in keeping its social media messages under control using quantitative content analysis of an NGO-promoted hashtag, #climatemarch, during a United Nations conference on climate change in 2015. Three dimensions of social media message success – volume, topic/valence, and participants – are proposed.